Clinicopathological features and outcomes in patients with concurrent medullary and papillary thyroid carcinoma - Sun, Ruonan; Liu, Xueting; Liu, Jiabin; Li, Zhihui; Wang, Yichao (Frontiers in Endocrinology, 2025)
ObjectiveThe co-existence of medullary thyroid carcinoma (MTC) and papillary thyroid carcinoma (PTC) is rare. The study analyzed the clinicopathological findings and prognosis of concomitant PTC in MTC patients.MethodsClinicopathological data and follow-up outcomes of 25 patients with concurrent medullary and papillary thyroid carcinoma (combination group) between January 2009 and May 2024 were collected and analyzed retrospectively. We compared clinicopathologic characteristics and follow-up outcomes between patients with concurrent MTC and PTC (combination group) and those with MTC alone (MTC group).ResultsThe 25 patients with concurrent MTC and PTC comprised 19 females and 6 males. There were no statistically significant differences between the combination group and the MTC group in terms of age, gender, or pathological features such as the diameter of MTC lesions, multifocality, extra-thyroidal extension (ETE), number of lymph node (LN) resected, the number of LN metastasis, the maximum diameter of LN metastasis, and TNM staging. The recurrence rate was similar between the two groups. Univariate analysis showed that the max tumor diameter, capsule invasion, extracapsular invasion and recurrent nerve invasion were associated with the risk of biochemical/structural abnormalities in MTC group. Multivariate analysis showed that only the max tumor diameter and capsule invasion were significant independent prognostic factors for biochemical/structural abnormalities.ConclusionThe result of this comparative study between patients with MTC and PTC co-existence and those with MTC alone showed similar invasiveness and prognosis.